The plastisphere and river systems as reservoirs for antibiotic resistant bacteria - Alfonsi, Soraya; Racciatti, Francesca; Guzman, Frank; Fabbretti, Attilio; Milon, Pohl; Vitali, Luca Agostino; Spurio, Roberto; Petrelli, Dezemona (Frontiers in Microbiology, 2026)
Antimicrobial resistance (AMR) is a critical global health threat. This phenomenon involves the diffusion of bacteria and genes among humans, animals and the environment. In particular, the presence of third generation cephalosporin (3GC)-resistant Enterobacteriaceae in natural environments is of high concern as they are classified as critical-priority pathogens of public health importance. In this work we studied the relation among plastic pollution in freshwater ecosystems, the spread of multidrug-resistant (MDR) bacteria and diffusion of antibiotic resistance genes (ARGs). Caged plastic fragments were deliberately introduced in a river of central Italy. Plastic samples were collected and analyzed in parallel with river water samples. Out of 267 cefotaxime (CTX) resistant isolates obtained, 65 CTX-resistant Enterobacteriaceae were selected for further analysis. Most of the isolates (75% of plastic-derived and 84% of water-derived isolates) were MDR with seven being carbapenem-resistant enterobacteria (CRE). Five of them synthesize KPC (Klebsiella pneumoniae carbapenemases) enzymes, and two strains were positive for metallo-β-lactamases (NDM). Among the KPC producers, three isolates were identified as K. pneumoniae sequence type ST1519. Their isolation in a natural ecosystem is alarming because they can potentially re-enter human populations through environmental pathways. Shotgun metagenomic analysis provided a comprehensive snapshot of the microbial communities associated to the plastisphere, revealing dominance of families such as Comamonadaceae, Sphaerotilaceae, and Flavobacteriaceae, which play key roles in environmental biofilm formation and stability. The resistome analysis highlighted the presence of ARGs conferring resistance to clinically important antibiotics, such as beta-lactams, vancomycin, and tetracyclines, alongside mobile genetic elements (MGEs) such as integrons, which facilitate the horizontal transfer of resistance genes. This study provides crucial experimental evidence that riverine plastic debris acts as a genetic reservoir and could act as an efficient vehicle for the accumulation and transfer of clinically relevant resistance determinants.